2016
DOI: 10.1371/journal.pone.0163257
|View full text |Cite
|
Sign up to set email alerts
|

Association between P16INK4a Promoter Methylation and Ovarian Cancer: A Meta-Analysis of 12 Published Studies

Abstract: BackgroundOvarian cancer is the primary cause of death in women diagnosed with gynecological malignancies worldwide. Absence of early symptoms prevents prompt diagnosis or successful therapeutic intervention. P16INK4a is a well-known tumor suppressor gene (TSG). Aberrant methylation of TSG promoter is an important epigenetic silencing mechanism leading to ovarian cancer progression. Studies have reported differences in methylation frequencies of the p16INK4a promoter between ovarian cancer and the correspondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Compared with previous meta-analyses,31,32 our meta-analysis had several improvements. First, the development of ovarian cancer is a multistep procedure involving normal tissues, benign disease, LMP or borderline tumor, and malignant tumor 20.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Compared with previous meta-analyses,31,32 our meta-analysis had several improvements. First, the development of ovarian cancer is a multistep procedure involving normal tissues, benign disease, LMP or borderline tumor, and malignant tumor 20.…”
Section: Discussionmentioning
confidence: 85%
“…P16 INK4a , which resembles classic TSGs such as P53 , is an important negative regulator of cell growth and proliferation 16. It has been synthetically evaluated for aberrant P16 INK4a methylation in numerous cancers,5154 including ovarian cancer 31,32. Considering the conflicting conclusions in two meta-analyses and the lack of comprehensive assessment on the role of methylated P16 INK4a in ovarian cancer, we performed an adaptive synthesized analysis to investigate the relationships between P16 INK4a promoter methylation and ovarian cancer risk, as well as clinicopathological features and prognostic value in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The other is the gene P16INK4a. A meta-study from 2016, including 612 OC patients and 289 controls from 12 studies, confirmed that P16INK4a promoter hypermethylation is found regularly in OC while rarely found in controls (21).…”
Section: Dna Hypermethylation In Ocmentioning
confidence: 81%
“…One of the earliest proofs that erroneous DNA methylation is directly involved in carcinogenesis came in 1994, when Herman et al showed that the tumor suppressor gene VHL might be silenced by hypermethylation of its promotor in some cases of renal carcinomas (19). Since then, numerous similar studies has shown that promotor hypermethylation is a widespread mechanism for silencing of tumor suppressor genes in human cancers, and it is estimated to be as common as mutation (20,21). Cancer related DNA methylation is often observed earlier than the actual neoplastic transformation, and it has been suggested that DNA methylation is a primary link between environment and cancer, as there seems to be a connection between lifestyle and cancer related DNA methylation in un-symptomatic persons (22,23).…”
Section: Dna Methylation In Cancermentioning
confidence: 99%
“…However, erroneous changes in DNA methylation-patterns are often seen in carcinogenesis [37] . Increasing levels of DNA methyltransferase and localized hypermethylation has been observed, especially in the promotors of tumor suppressors [38] , [39] . However, reduced methylation of oncogene promoters or genome wide hypomethylation, resulting in chromosome instability, has also been observed in cancer [40] , [41] .…”
Section: Methods and Designmentioning
confidence: 99%